2012
DOI: 10.1063/1.4745866
|View full text |Cite
|
Sign up to set email alerts
|

Resonant splitting in periodic T-shaped photonic waveguides

Abstract: Abstract:Resonant splitting phenomena of photons in periodic T-shaped waveguide structure are investigated by the Green's function method. An interesting resonant phenomenon is found in the transmission spectra. When the T-shaped structure contains n constrictions, there are (n-1)-fold resonant splitting peaks in the low frequency region. The peaks are induced by low quasi-bound states in which photons are intensively localized in the stubs. While (n-2)-fold resonant splitting occurs in the high frequency regi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Generally, the cation B occupies the octahedral center with six nearest neighbor halide atoms surrounded. Although interactions between cation A and surrounding BX 6 octahedron are weak, many interesting electronic structural properties appear due to this particular atomic configuration, such as tunable band gap, [43][44][45][46][47] and optical absorption (see below). Furthermore, it is found that the cation A plays a significant role in maintaining the structure stability and adjusting the B-X bond length which determines the nature of the band edge, especially the band gap.…”
Section: Structure and Electronic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the cation B occupies the octahedral center with six nearest neighbor halide atoms surrounded. Although interactions between cation A and surrounding BX 6 octahedron are weak, many interesting electronic structural properties appear due to this particular atomic configuration, such as tunable band gap, [43][44][45][46][47] and optical absorption (see below). Furthermore, it is found that the cation A plays a significant role in maintaining the structure stability and adjusting the B-X bond length which determines the nature of the band edge, especially the band gap.…”
Section: Structure and Electronic Propertiesmentioning
confidence: 99%
“…Furthermore, it is found that the cation A plays a significant role in maintaining the structure stability and adjusting the B-X bond length which determines the nature of the band edge, especially the band gap. [43][44][45][46][47] In the past, researchers have introduced a large number of organic amine cations to occupy the A position, including methylammonium Figure 1B. 38 However, in order to maintain the ideal cubic structure, perovskite has to meet the condition, that is, the Goldschmidt tolerance factor t (t…”
Section: Structure and Electronic Propertiesmentioning
confidence: 99%